2016
DOI: 10.1038/srep27400
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Defects in Synaptic Differentiation of Neocortical Neurons in Response to Prenatal Valproate Exposure

Abstract: Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental disorders characterized by impairments in social interactions and stereotyped behaviors. Valproic acid (VPA) is frequently used to treat epilepsy and bipolar disorders. When taken during pregnancy, VPA increases the risk of the unborn child to develop an ASD. In rodents, in utero VPA exposure can precipitate behavioral phenotypes related to ASD in the offspring. Therefore, such rodent models may allow for identification of synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
5
23
2
Order By: Relevance
“…Of note, the absence of PV not only affects the output of the FSI, but also entails modifications in synaptic transmission between the cortical afferences and striatal FSI; in PV -/- mice short-term depression of EPSCs is increased in a similar time window (Wohr et al, 2015) as short-term facilitation is increased in PV-FSI (Orduz et al, 2013). We did not detect altered levels of PV in the forebrain samples of VPA mice, in contrast to recent findings by Iijima et al (2016), who reported a decrease in PV levels by >20% in lysates from neocortical cortex of PND15-21 mice. This apparent discrepancy might be related to the time point of their analyses: in the period from PND15-25, PV protein levels, the number of PV-immunoreactive neurons or of Pvalb neuron structures (e.g., boutons) increase considerably, e.g., seen in mouse or rat cortex (Alcantara et al, 1993; de Lecea et al, 1995; Huang et al, 1999), hippocampus (de Lecea et al, 1995; Chen et al, 2014), and cerebellar Pvalb neurons (Collin et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Of note, the absence of PV not only affects the output of the FSI, but also entails modifications in synaptic transmission between the cortical afferences and striatal FSI; in PV -/- mice short-term depression of EPSCs is increased in a similar time window (Wohr et al, 2015) as short-term facilitation is increased in PV-FSI (Orduz et al, 2013). We did not detect altered levels of PV in the forebrain samples of VPA mice, in contrast to recent findings by Iijima et al (2016), who reported a decrease in PV levels by >20% in lysates from neocortical cortex of PND15-21 mice. This apparent discrepancy might be related to the time point of their analyses: in the period from PND15-25, PV protein levels, the number of PV-immunoreactive neurons or of Pvalb neuron structures (e.g., boutons) increase considerably, e.g., seen in mouse or rat cortex (Alcantara et al, 1993; de Lecea et al, 1995; Huang et al, 1999), hippocampus (de Lecea et al, 1995; Chen et al, 2014), and cerebellar Pvalb neurons (Collin et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…This decrease was also confirmed at the protein level: K v 3.1b protein levels determined by Western blot analysis were decreased to a similar extent, i.e., ∼40% reduction ( p = 0.0002) of K v 3.1b in forebrain samples of VPA mice compared to controls ( Figure 5B2 ), a finding in line with previous results from lysates of SSC of PND15-21 VPA mice (Iijima et al, 2016). We estimate that these results reflect decreased expression of K v 3.1 channels rather than loss of neurons expressing K v 3.1, since the overlap between cortical Pvalb neurons (unchanged in mPFC and SSC; Figures 3A and 4A ) and K v 3.1b is >95% (Chow et al, 1999).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations